Vancomycin-resistant Enterococcus faecium colonizing patients on hospital admission in Germany: prevalence and molecular epidemiology. (22nd July 2020) - Xanthopoulou, Kyriaki; Peter, Silke; Tobys, David; Behnke, Michael; Dinkelacker, Ariane G; Eisenbeis, Simone; Falgenhauer, Jane; Falgenhauer, Linda; Fritzenwanker, Moritz; Gölz, Hannah; Häcker, Georg; Higgins, Paul G; et al.
Abstract: Objectives: To analyse the rectal carriage rate and the molecular epidemiology of vancomycin-resistant Enterococcus faecium (VREfm) recovered from patients upon hospital admission. Methods: Adult patients were screened at six German university hospitals from five different federal states upon hospital admission for rectal colonization with VREfm between 2014 and 2018. Molecular characterization of VREfm was performed by WGS followed by MLST and core- genome MLST analysis. Results: Of 16350 patients recruited, 263 were colonized with VREfm, with increasing prevalence rates during the 5 year study period (from 0.8% to 2.6%). In total, 78.5% of the VREfm were vanB positive and 20.2% vanA positive, while 1.2% harboured both vanA and vanB . The predominant ST was ST117 (56.7%) followed by ST80 (15%), ST203 (10.9%), ST78 (5.7%) and ST17 (3.2%). ST117/ vanB VREfm isolates formed a large cluster of 96 closely related isolates extending across all six study centres and four smaller clusters comprising 13, 5, 4 and 3 isolates each. In contrast, among the other STs inter-regional clonal relatedness was rarely observed. Conclusions: To our knowledge, this is the largest admission prevalence and molecular epidemiology study of VREfm. These data provide insight into the epidemiology of VREfm at six German university hospitals and demonstrate the remarkable inter-regional clonal expansion of the ST117/ vanB VREfm clone.